Alternatif Lokasi Terminal Sebagai Pusat Pertumbuhan Ekonomi di Doloksanggul Kabupaten Humbang Hasundutan - Jusmar Effendi Simamora; Asnawi Asnawi (Department of Urban and Regional Planning, Diponegoro University, 2014)
Doloksanggul as the Capital District of Humbang Hasundutan also as the center economic growth until now has not had a terminal infrastructure. The result appears terminal shadows that make the city crowded and poor quality of public transport services, so that the internal and external connectivity hub disrupted economic growth. While the terminal as one element of ground transportation can lead to multiple economic effects (multiplier effect) to the local and regional economy, so it has a very strategic role in supporting economic growth centers. This study aims to determine the location of the terminal is capable of supporting Doloksanggul as the center of economic growth in the District Humbang Hasundutan through assessment criteria used. To achieve the research objectives used a qualitative-descriptive and quantitative-descriptive approach which is using purposive sampling techniques, by restricting the respondent only directly related to the problem, namely regulators, operators and users (passengers). The analytical method used is the method of Analytic Hierarchy Process (AHP), because it is a flexible method of decision-making by combining a variety of considerations to obtain multi-criteria problem solving. The formulated criteria are the easies of accessibility to enter and from the terminal location, the availability of transportation networks, the ultimate destination of public transport track AKAP/AKDP, adjacent to the central market, located in the city center. The alternatives terminal location are located in the Bonanionan village, the Pasaribu village and the Simangaronsang village. Based on the results of the analysis found that the best location is the Bonanionan village with value of 0.6022 (60.22%) followed the Pasaribu village with value of 0.3073 (30.73%) and the last is the Simangaronsang village with value of 0.0905 (9.05%).